2016
DOI: 10.21699/jns.v5i4.431
|View full text |Cite
|
Sign up to set email alerts
|

Varied Presentation of Congenital Segmental Dilatation of the Intestine in Neonates: Report of Three Cases

Abstract: Congenital segmental dilatation (CSD) of the intestine is a rare developmental anomaly characterized by sharply demarcated dilatation of a gastrointestinal segment and may present with intestinal obstruction. We report three cases of CSD of the intestine in neonates with varied presentation. First patient was mistaken as pneumoperitoneum on abdominal radiograph, which led to initial abdominal drain placement. The 2nd patient was a case of anorectal malformation associated with congenital pouch colon (CPC) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
0
8
0
3
Order By: Relevance
“…In the last couple of decades, the criteria became stricter and, since 2008, to the best of our knowledge, 20 adequately described cases have been reported in the English literature. 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 Here, we report on four infants with CSID with segmental dilatation located in the duodenum, ileum, ascending colon, and sigmoid colon. Two of our infants showed additional intestinal anomalies, but remarkably, all four patients had cardiovascular defects, and this is the first report demonstrating such a consistent association in four consecutive cases.…”
Section: Discussionmentioning
confidence: 93%
“…In the last couple of decades, the criteria became stricter and, since 2008, to the best of our knowledge, 20 adequately described cases have been reported in the English literature. 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 Here, we report on four infants with CSID with segmental dilatation located in the duodenum, ileum, ascending colon, and sigmoid colon. Two of our infants showed additional intestinal anomalies, but remarkably, all four patients had cardiovascular defects, and this is the first report demonstrating such a consistent association in four consecutive cases.…”
Section: Discussionmentioning
confidence: 93%
“…[4] Finding merely case reports and small case series in the literature vindicates its scarcity. [6] Sakaguchi et al identified 28 cases in a nationwide survey of Japan, over a decade period. [4] We also published a case report in 2012 and a series of 3 cases in 2016.…”
Section: Discussionmentioning
confidence: 99%
“…[4] We also published a case report in 2012 and a series of 3 cases in 2016. [3,6] Two patterns of presentation exist: early with neonatal intestinal obstruction; and late with chronic constipation and related sequelae such as failure to thrive, malnutrition, malabsorption, anemia, etc. [2,4,7,8] Ileal segmental dilatation usually presents early whereas colonic segmental dilatation appears to escape the early presentation, though not a rule.…”
Section: Discussionmentioning
confidence: 99%
“…This was not necrotizing enterocolitis or spontaneous intestinal perforation [3] or segmental intestinal dilatation [4], which does not resolve spontaneously and may itself cause intestinal obstruction. This was something different; and hence, my puzzlement!…”
Section: Dear Editormentioning
confidence: 99%